Intercalation‐Driven Reversible Control of Magnetism in Bulk Ferromagnets. (3rd March 2014) - Dasgupta, Subho; Das, Bijoy; Knapp, Michael; Brand, Richard. A.; Ehrenberg, Helmut; Kruk, Robert; Hahn, Horst
<x xml:space="preserve">Abstract</x> An extension in magnetoelectric effects is proposed to include reversible chemistry‐controlled magnetization variations. This ion‐intercalation‐driven magnetic control can be fully reversible and pertinent to bulk material volumes. The concept is demonstrated for ferromagnetic iron oxide where the intercalated lithium ions cause valence change and partial redistribution of Fe3+ cations yielding a large and fully reversible change in magnetization at room temperature. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>